2017
DOI: 10.1136/acupmed-2016-011082
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Dry Needling in Patients with Upper Trapezius Myofascial Trigger Points

Abstract: BackgroundActive myofascial trigger points (MTrPs) are major pain generators in myofascial pain syndrome. Dry needling (DN) is an effective method for the treatment of MTrPs.ObjectiveTo assess the immediate neurophysiological and clinical effects of DN in patients with upper trapezius MTrPs.MethodsThis was a prospective, clinical trial study of 20 patients with upper trapezius MTrPs and 20 healthy volunteers (matched for height, weight, body mass index and age), all of whom received one session of DN. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 41 publications
(27 reference statements)
0
24
0
1
Order By: Relevance
“…The first mechanical effect was supported by the hypothesis that TrP-DN is able to reduce endplate noise characteristicof the TrP area 71. Some studies have confirmed that TrP-DN decreases the amplitude and frequency of end plate noise and end plate spike, ie, typical sponteneous electrical activity features of TrPs, decreases the acetylcholine levels72,73 and the neuromuscular junction response 74. A decrease in end plate noise and end plate spike after the application of TrP-DN would support an effect on the motor end plate.…”
Section: Mechanisms Underlying Trigger Point Needling Therapymentioning
confidence: 95%
“…The first mechanical effect was supported by the hypothesis that TrP-DN is able to reduce endplate noise characteristicof the TrP area 71. Some studies have confirmed that TrP-DN decreases the amplitude and frequency of end plate noise and end plate spike, ie, typical sponteneous electrical activity features of TrPs, decreases the acetylcholine levels72,73 and the neuromuscular junction response 74. A decrease in end plate noise and end plate spike after the application of TrP-DN would support an effect on the motor end plate.…”
Section: Mechanisms Underlying Trigger Point Needling Therapymentioning
confidence: 95%
“…Por otra parte, Furlan y cols. (29) proponen que la PS estimula las interneuronas inhibitorias, evitando la transmisión normal del dolor a la corteza sensorial, inclusive asociándose a la teoría del Gate Control (18). Por último, Shah y cols., en estudios experimentales in vivo, mencionan que la PS puede puede corregir el entorno químico alterado que se encuentra en el PGM, logrando normalizar el estado del músculo (30,31).…”
Section: Resultsunclassified
“…The aim of this randomized controlled trial was to evaluate the therapeutic effect of superficial acupuncture for treating myofascial pain syndrome in the upper trapezius muscle. Direct needling in the trigger point, as in Ah shi point acupuncture in Eastern medicine or dry needling in Western medicine, has been proven as an effective therapy for myofascial pain [9, 1720]. In many cases, superficial acupuncture has been used as a sham control [21, 22].…”
Section: Discussionmentioning
confidence: 99%